Anterior fusion surgery with overcorrection in the treatment of adolescent idiopathic scoliosis with Lenke 1 AR curve type: how to achieve overcorrection and its effect on postoperative spinal alignment - Nobuki Tanaka; Satoshi Inami; Hiroshi Moridaira; Tsuyoshi Sorimachi; Haruki Ueda; Hiromichi Aoki; Satoshi Takada; Yutaka Nohara; Hirotaka Haro; Hiroshi Taneichi (BMC Musculoskeletal Disorders, 2023)
Abstract Background The efficacy of anterior fusion with overcorrection in the instrumented vertebra for Lenke 1 AR type curves has been reported, but how to achieve overcorrection and how overcorrection affects spinal alignment are unclear. The purpose of this study was to identify the factors that cause overcorrection, and to investigate how overcorrection affects postoperative spinal alignment in the surgical treatment of Lenke 1 AR type curves. Methods Patients who had anterior surgery for a Lenke type 1 or 2 and lumbar modifier AR (L4 vertebral tilt to the right) type scoliosis and minimum 2-year follow-up were included. The radiographic data were measured at preoperative, postoperative 1 month, and final follow-up. The UIV-LIV Cobb angle was determined as the Cobb angle between the upper instrumented vertebra (UIV) and the lower instrumented vertebra (LIV), and a negative number for this angle was considered overcorrection. The screw angle was determined to be the sum of the angle formed by the screw axis and the lower and upper endplates in the LIV and UIV, respectively. The change (Δ) in the parameters from postoperative to final follow-up was calculated. The relationships between the UIV-LIV Cobb angle and other radiographic parameters were evaluated by linear regression analyses. Results Fourteen patients met the inclusion criteria. Their median age was 15.5 years, and the median follow-up period was 53.6 months. The median UIV-LIV Cobb angle was –1.4° at postoperative 1 month. The median screw angle was 4.7°, and overcorrection was achieved in 11 (79%) cases at postoperative 1 month. The screw angle (r 2  = 0.42, p = 0.012) and Δ FDUV-CSVL (the deviation of the first distal uninstrumented vertebra from the central sacral vertical line, r 2  = 0.53, p = 0.003) were significantly correlated with the UIV-LIV Cobb angle. Conclusions Screw placement in the UIV and LIV not parallel to the endplate, but angled, was an effective method to facilitate overcorrection in the instrumented vertebrae. The results of the present study suggest that overcorrection could bring spontaneous improvement of coronal balance below the instrumented segment during the postoperative period.